Neural Substrates of the Drift-Diffusion Model in Brain Disorders - Ankur Gupta; Rohini Bansal; Hany Alashwal; Anil Safak Kacar; Fuat Balci; Fuat Balci; Ahmed A. Moustafa; Ahmed A. Moustafa; Ahmed A. Moustafa (Frontiers in Computational Neuroscience, 2022)
Many studies on the drift-diffusion model (DDM) explain decision-making based on a unified analysis of both accuracy and response times. This review provides an in-depth account of the recent advances in DDM research which ground different DDM parameters on several brain areas, including the cortex and basal ganglia. Furthermore, we discuss the changes in DDM parameters due to structural and functional impairments in several clinical disorders, including Parkinson's disease, Attention Deficit Hyperactivity Disorder (ADHD), Autism Spectrum Disorders, Obsessive-Compulsive Disorder (OCD), and schizophrenia. This review thus uses DDM to provide a theoretical understanding of different brain disorders.